Time is money: Real effects of relationship lending in a crisis - James, Christopher; Lu, Jing; Sun, Yangfan (Journal of Banking & Finance, 2021)
We provide evidence that small banks responded faster to Paycheck Protection Program (PPP) loan requests and lent more intensively to small businesses than larger banks. Using community bank pre-pandemic share of deposits/assets as an instrument for the intensity of PPP lending, we find a negative and significant relationship between county level bankruptcy filings and PPP lending per small business. Overall, our findings suggest that community banks remain an important conduit for small business credit particularly during crises when a rapid response is required.